2021
DOI: 10.1111/1440-1681.13481
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol protects against cyclophosphamide‐induced nephrotoxicity through modulation of oxidative stress, inflammation, and apoptosis

Abstract: The usefulness of cyclophosphamide (CP) in the treatment of multiple human malignancies and immunological diseases is hindered by the danger of developing nephrotoxicity. The toxic metabolites of CP are suggested to be responsible for oxidative stress resulted from the production of reactive oxygen species (ROS) and stimulation of lipid peroxidation. Nebivolol (NEB) is a third‐generation selective B1 adrenoceptor antagonist, but it has also various pharmacological properties such as anti‐inflammation, anti‐apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
(39 reference statements)
0
10
2
Order By: Relevance
“…As expected, mesna significantly reversed the CPX-induced changes, which was confirmed in the kidney score. In contrast to nebivolol [83], carvedilol did not attenuate significantly histological changes caused by CPX in kidneys, except for decreasing incidents of interstitial hemorrhages. It seems, however, that the presence of kidney pathologies does not 100% correlate with kidney function, as carvedilol alleviates CPX-induced changes in serum potassium and creatinine concentrations, which can be interpreted as improvement of kidney function.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…As expected, mesna significantly reversed the CPX-induced changes, which was confirmed in the kidney score. In contrast to nebivolol [83], carvedilol did not attenuate significantly histological changes caused by CPX in kidneys, except for decreasing incidents of interstitial hemorrhages. It seems, however, that the presence of kidney pathologies does not 100% correlate with kidney function, as carvedilol alleviates CPX-induced changes in serum potassium and creatinine concentrations, which can be interpreted as improvement of kidney function.…”
Section: Discussioncontrasting
confidence: 69%
“…Additionally, in groups receiving CPX, different levels of the swelling tubules were noticed. Similarly, other authors described swelling of proximal convoluted tubules, inflammatory cells infiltration, tubular and glomeruli atrophy, tubular degeneration, and dilatation in Bowman's capsules [76][77][78][79]83]. In contrast to our study, Dobrek et al [47] did not reveal any significant pathology in the rat kidneys after the same intraperitoneal dose of CPX.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…More interestingly, the markers of renal and cardiac damage were also altered indicating CYP-induced cardiorenal injury in this study. However, studies have shown that CYP could damage the heart 23 , kidney 4 5 , testis 6 24 , and bladder 3 . In this study, CYP prominently increased levels of urea, creatinine as well as activities of cardiac CK and LDH ( Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%